Solids Concentration and Solids Velocity in the Wall Region of Circulating Fluidzed Beds - Wirth, Karl-Ernst; et al. (Preprints 11th Internat. Conference on Fluidized Bed Combustion, 1991)
In circulating fluidized beds, heat is transferred to the watersteam-system by wall heat exchangers. In order to understand both the heat transfer process and the erosion of the heat exchanger it is particularly interesting to know the solids concentration and the solids velocity near the wall of the circulating fluidized bed. Two systems for measuring these quantities were developed. The principle of the measurement of the solids concentration is based on the attenuation of a γ-beam passing the circulating fluidized beds. Shifting the radiation source and the detector across the cross-section of the circulating fluidized bed it was possible to measure the radial solids concentration profile. The experiments showed that the solids concentration in the wall region is about three times as large as that in the core region of the bed and that a small layer free of solids and about 1 mm thick exists immediate near the wall. This measuring system is applicable in industrial fluidized bed combusters, because no part of the systems is placed in the bed. The velocity was measured by using a phosphorescent material. A small part of this material was marked by a light flash and then traced with a video camera. We observed that all the material immediate near the wall is falling down and the velocity of this falling film is in the order of one to three meter per second.
UnivIS-Import:2015-04-16:Pub.1991.tech.ITC.mechve.solids
Keywords: fluidized; bed; combustion